2017
DOI: 10.48550/arxiv.1709.00641
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Marginal and dependence uncertainty: bounds, optimal transport, and sharpness

Abstract: Motivated by applications in model-free finance and quantitative risk management, we consider Fréchet classes of multivariate distribution functions where additional information on the joint distribution is assumed, while uncertainty in the marginals is also possible. We derive optimal transport duality results for these Fréchet classes that extend previous results in the related literature. These proofs are based on representation results for increasing convex functionals and the explicit computation of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The difference between Assumption 2.1 and the no-arbitrage assumption in [15] is that the price of a financial derivative in the present work is not a singleton but can lie anywhere between the corresponding bid and ask prices π, π. Note that there are other notions of no-arbitrage that are weaker than Assumption 2.1, for example the "no uniform strong arbitrage" assumption in Definition 2.1 of Bartl et al [4].…”
Section: Duality In the Presence Of Option-implied Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference between Assumption 2.1 and the no-arbitrage assumption in [15] is that the price of a financial derivative in the present work is not a singleton but can lie anywhere between the corresponding bid and ask prices π, π. Note that there are other notions of no-arbitrage that are weaker than Assumption 2.1, for example the "no uniform strong arbitrage" assumption in Definition 2.1 of Bartl et al [4].…”
Section: Duality In the Presence Of Option-implied Informationmentioning
confidence: 99%
“…The setting of dependence uncertainty is intimately linked with optimal transport theory, and its tools have also been used in order to derive bounds for multi-asset option prices, see e.g. Bartl, Kupper, Lux, Papapantoleon, and Eckstein [4] for a formulation in the presence of additional information on the joint distribution. More recently, Aquino and Bernard [2], Eckstein and Kupper [32] and Eckstein, Guo, Lim, and Oblój [34] have translated the model-free superhedging problem into an optimization problem over classes of functions, by extending results in optimal transport, and used neural networks and the stochastic gradient descent algorithm for the computation of the bounds.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, Lux and Papapantoleon [12] showed that for d > 2, the improved Fréchet-Hoeffding bounds are copulas only in trivial cases and proper quasi-copulas otherwise. Moreover, Bartl, Kupper, Lux, Papapantoleon, and Eckstein [1] showed that the improved Fréchet-Hoeffding bounds are not pointwise sharp (or best-possible), even in d = 2, if the aforementioned 'monotonicity' conditions are violated.…”
Section: Copulas Quasi-copulas and Improved Fréchet-hoeffding Boundsmentioning
confidence: 99%
“…In contrast, Lux and Papapantoleon [24] showed that for d > 2 the bounds Q S,Q * and Q S,Q * are copulas only in degenerate cases, and quasi-copulas otherwise. Moreover, Bartl, Kupper, Lux, and Papapantoleon [2] recently showed that once the constraints of [4,43] are violated then the improved Fréchet-Hoeffding bounds fail to even be pointwise sharp, still in dimension d = 2.…”
Section: Improved Fréchet-hoeffding Bounds Using Subsetsmentioning
confidence: 99%